2014
DOI: 10.1155/2014/609708
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Marchiafava-Bignami Syndrome: A Cornerstone in Diagnosis and Prognosis

Abstract: Marchiafava-Bignami syndrome is a rare condition. However, with the advent of MRI, more and more of these cases are being diagnosed. Thus, it becomes essential for a radiologist to be familiar with its imaging features as well as clinical presentation. A 50-year-old chronic alcoholic presented to the emergency room with history of 3 episodes of seizures 2 days earlier. The patient had gait disturbances for the last few days. On examination, the patient was in a state of stupor. No neck rigidity was elicited. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…[ 15 – 19 ] MRI plays a dominant role in the early diagnosis of MBD, facilitates early invention of acute MBD, and also predicts its prognosis. [ 20 ] (Supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 – 19 ] MRI plays a dominant role in the early diagnosis of MBD, facilitates early invention of acute MBD, and also predicts its prognosis. [ 20 ] (Supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…T2 and Fluid Attenuated Inversion Recovery (FLAIR) weighted sequences confirmed hyperintense lesions of the splenium and the body of corpus callosum, with relative sparing of the dorsal and ventral layers, which represented the typical "sandwich sign" (Figure 3) [2]. In FLAIR images, the frontal cortical-sottocortical lesions seen on the CT scan were evident as hyperintense areas (Figure 4).…”
Section: Case Reportmentioning
confidence: 91%
“…On the other hand, ADEM causes individually large, asymmetric lesions and involvements in marchiafava bignami disease were large, often symmetrically in the midline of the splenium and did not reach the edge of the CC. [5,27] Central CC volume along with medulla oblongata volume can help discriminate between different subtypes of MS. Various subtypes of MS affect different neuroanatomical regions of the CC differently.…”
Section: In Multiple Sclerosis Mrimentioning
confidence: 99%
“…General pattern of CC pathology in MBD is hyperintensity on flair imaging and sometimes hemispheric white matter, reflecting damage to myelin and vasogenic edema of the CC and extracallosal projections. [27] Because of pathological variety of this disorder there is no certain sequence and pattern of pathology of CC in MBD. Some studies showed that involvement of the CC in MBD was initially in the genu, without significant association with DTI changes of CC and NAWM.…”
Section: Marchiafava Bignamimentioning
confidence: 99%
See 1 more Smart Citation